No place like home? Surveillance and what home means in old age - Ben Mortenson, W. (Can J Aging, 2016)
New surveillance technologies like those included in ambient assisted living are being developed to improve the security and safety of ‘at risk’ older people, but ethical questions have been raised about the extent to which they compromise the rights and privacy of the people being monitored. A qualitative study was conducted to understand the ways these novel surveillance technologies would influence their everyday experiences of home. Participants felt new forms of surveillance would influence their sense of security, autonomy, and self-confidence, and would alter perceptions of home. The findings emphasize the need to improve our understanding of how ambient assisted living will affect the lives of those being monitored.